2018
DOI: 10.1186/s12931-018-0922-9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of viral infection on the relationships between airway cytokines and lung function in asthmatic children

Abstract: BackgroundFew longitudinal studies examine inflammation and lung function in asthma. We sought to determine the cytokines that reduce airflow, and the influence of respiratory viral infections on these relationships.MethodsChildren underwent home collections of nasal lavage during scheduled surveillance periods and self-reported respiratory illnesses. We studied 53 children for one year, analyzing 392 surveillance samples and 203 samples from 85 respiratory illnesses. Generalized estimated equations were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…Apart from iNOS induction in response to viruses and viral components, interferon gamma has been reported as a major cytokine to induce iNOS and NO overproduction in the pathogenesis of virus infection [ 123 , 124 ]. This cytokine is associated to Th1 cell response, as it is acknowledged that antiviral adaptive response is Th1 type [ 125 ]. Nevertheless, some viruses (such as influenza virus and HSV) might inhibit Th1 response through downregulation of interferons production.…”
Section: Molecular Mechanisms Of Ros and Rns Generation In Response T...mentioning
confidence: 99%
“…Apart from iNOS induction in response to viruses and viral components, interferon gamma has been reported as a major cytokine to induce iNOS and NO overproduction in the pathogenesis of virus infection [ 123 , 124 ]. This cytokine is associated to Th1 cell response, as it is acknowledged that antiviral adaptive response is Th1 type [ 125 ]. Nevertheless, some viruses (such as influenza virus and HSV) might inhibit Th1 response through downregulation of interferons production.…”
Section: Molecular Mechanisms Of Ros and Rns Generation In Response T...mentioning
confidence: 99%
“…Children are especially susceptible to acute wheezing episodes caused by RV. To date, most studies in children have examined immune profiles associated with wheeze in the blood [19][20][21][22] , examined nasal gene expression using transcriptomic methods 23,24 , focused on targeted nasal cytokines [24][25][26][27] , or utilized univariate analytical methods. 28 Given that different asthma endotypes are known to exist, we theorized that a comprehensive assessment of nasal mediators was warranted in the context of RV infection, including examination of relationships to viral load, allergic status, and respiratory symptoms.…”
Section: Key Messagesmentioning
confidence: 99%
“…The researchers observed that wheezing with rhinovirus was associated with asthma at age 13 (OR = 3.3, 95% CI (1.5-7.1), p = 0.02) and sensitization to allergens increased with age [9]. FEV 1 % predicted has also been shown to be lower in asthmatic patients admitted to the hospital with an asthma exacerbation with concurrent rhinovirus infection, compared to children with asthma admitted for an exacerbation but negative for rhinovirus [29,59].…”
Section: Rhinovirusmentioning
confidence: 99%